Albizia Benth Oil Maleinised Polyesteramides: Synthesis, Structure, and Characteristics. (22nd May 2012) - Akintayo, C. O.; Akintayo, E. T.; Azeez, M. A.
Abstract : Albizia benth oil (ABO) has been employed in the preparation of polyesteramide resin via the condensation of hydroxyethylamide derivatives of ABO fatty acids and phthalic anhydride. The maleinised Albizia benth oil polyesteramide was prepared, using maleinised hydroxyethylamide derivatives of ABO obtained by appending maleate half esters onto the hydroxyethylamide derivative of ABO and phthalic anhydride. Structural elucidation and characterisation of the products carried out revealed that maleic anhydride can successfully be used to modify polyesteramides, to improve its properties such as drying, flexibility, scratch hardness, impact resistance, chemical resistance, and lower curing temperature.